The Role Of Notaries In Land Dispute Resolution Through Alternative Mediation And Arbitration - Ladynanti, Prizqa (INFOKUM, 2024)
Land dispute resolution in Indonesia often faces various obstacles, Challenges faced in resolving land disputes include taking a long time, expensive costs, and not always resulting in a satisfactory settlement for all parties. Therefore, the role of notaries in resolving land disputes through alternative channels such as mediation and arbitration provides significant advantages, including time and cost efficiency, as well as maintaining good relations between the parties involved. With the authority to make authentic deeds, notaries not only ensure the legality of documents, but also act as neutral mediators in conflicts involving administrative, civil, and criminal aspects. Their unique position allows them to facilitate effective communication between the parties to the dispute, guiding them towards an amicable solution. This study examines the diverse roles of notaries in land dispute resolution, emphasizing their ability to simplify the process and provide legal certainty. By leveraging their expertise in legal documentation and mediation techniques, notaries contribute to a more harmonious approach to conflict resolution, fostering cooperation and understanding among the parties to the dispute while ensuring that the agreements made are legally binding. This study aims to examine the role of notaries in helping the parties reach a mutual agreement and resolve land disputes. The results of the study show that mediation and arbitration conducted by notaries not only speed up the dispute resolution process, but also provide better legal certainty for the parties.